Policy and practice of inclusive education for mainstream secondary teachers supporting learners with physical disabilities in the Lower Shire, Malawi - De Souza, Ben (Rhodes University, Faculty of Education, Department of Education, 2021)
The Government of Malawi and its education partners are currently implementing the National Education Policy (2016) and the National Strategy on Inclusive Education (2017-2021). My study explored how mainstream secondary teachers interpret policies and strategies, and transition to the practice of supporting learners with physical disabilities. Previous studies revealed policy-to-practice disparities in the Malawian inclusive secondary education but did not proffer teacher-oriented strategies that can mitigate the disparities and enhance inclusive education. My study argued that effective strategies that could lessen policy-to-practice mismatches and advance inclusive education primarily rest with mainstream teachers, as they mediate policy and practice. This study drew on Clough and Corbett's disability studies critique and Urie Bronfenbrenner's bioecological systems perspective to form theoretical and analytical frameworks for understanding the problem and discussing the findings. The study generated primary data from the Lower Shire districts of Chikwawa and Nsanje in Malawi. Thirty-three teachers, randomly selected from four schools, responded to questionnaires. In-depth, face to face interviews were conducted with purposely selected teachers from the same four schools. The study also generated secondary data from a review of policy documents. The findings showed that policy directives are shifting inclusive education from social perspectives to political perspectives, whereby mainstream teachers regard national policies and strategies as political responses to demands for inclusion. The findings further showed that teachers' practices are moving away from the provision of special needs to the promotion of inclusive needs, whereby inclusive education benefits all learners. The study found that some teachers are resisting inclusive education, and would like learners with physical disabilities to return to special schools, thus controverting policy directives. As a way forward, this study recommended that future policy formulation and implementation in the Malawian mainstream secondary education should consider the bioecological systems approach, whereby policymakers systematically interact with the mainstream secondary teachers to improve their perspectives, competencies and practices on inclusive education.
Keywords: Children with disabilities -- Education (Secondary) -- Malawi; Children with disabilities -- Education -- Government policy -- Malawi; Children with disabilities -- Legal status, laws, etc. -- Malawi; Inclusive education -- Malawi; Teachers -- Training of -- Malawi; High School teachers -- Malawi -- Attitudes